2008
DOI: 10.1001/archpsyc.65.5.513
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Study of First Onset and Chronicity in Major Depressive Disorder

Abstract: Major depressive disorder is unremitting in 15% of cases and recurrent in 35%. About half of those with a first-onset episode recover and have no further episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
376
5
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 513 publications
(419 citation statements)
references
References 57 publications
(59 reference statements)
23
376
5
15
Order By: Relevance
“…El porcentaje de síntomas catatónicos y característi-cas atípicas se enmarcan dentro de lo descrito 30,33 . Dado que la muestra está conformada por pacientes graves y/o con falta de respuesta terapéutica, se esperaba este porcentaje de EDM crónicos (26,8%) superior al de la población general (15%) 34 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El porcentaje de síntomas catatónicos y característi-cas atípicas se enmarcan dentro de lo descrito 30,33 . Dado que la muestra está conformada por pacientes graves y/o con falta de respuesta terapéutica, se esperaba este porcentaje de EDM crónicos (26,8%) superior al de la población general (15%) 34 .…”
Section: Discussionunclassified
“…Si bien nuestro estudio es corto en seguimiento para recurrencia y cronicidad, la tendencia de la remisión más lo publicado por otros autores reafirman la cronicidad y menor respuesta terapéutica en un grupo de pacientes 19,21,34,46 .…”
Section: Discussionunclassified
“…These disorders tend to have a relapsing course ; in the large UK birth cohort that has been followed to the age of 53, 70 % of adolescents who had emotional disorders at both ages 13 and 15 had mental disorders at age 36, 43 or 53, compared with about 25 % of the mentally healthy adolescents (Colman et al 2007). Studies of single disorders tend to have a shorter follow-up period, and depend on the severity of the first episode of disorder ; thus, Eaton et al (2008) followed first episodes of depression in a community sample for at least 13 years and showed that half had only a single episode, whereas 35 % had recurrent episodes and 15 % were unremitting. Brodaty et al (2001) followed depressives who had been admitted to hospital for 25 years, and showed that only 12 % had recovered and were well whereas 84 % had had recurrences.…”
Section: Coursementioning
confidence: 99%
“…almost 75 % were in-patients, 90 % probable or definite endogenous subtype ; Solomon et al 2000), and are subject to biases that almost without question inflate these recurrence estimates (e.g. Berkson bias, the ' clinician's illusion ' ; Berkson, 1946 ;Cohen & Cohen, 1984 Baltimore site of the Epidemiologic Catchment Area (ECA) Study culled out 92 cases with a first lifetime onset of MDD occurring over a minimum follow-up period of 13 years (Eaton et al 2008). This latter investigation, using a population-based sample, provides an important counterpart to other studies on the lifetime course of depression.…”
mentioning
confidence: 99%
“…The question needs to be enlarged to face the inconvenient but inescapable fact that depression can be either, that depression as we currently conceive and define the condition is ' both '. The evidence is prima facie : approximately half of people who become depressed never do so again, and approximately half do (Eaton et al 2008). In recognizing and resolving this seeming paradox, and by adding the acute depressive conditions that do not recur to the research agenda, early indices of recurrence risk may be found, and the trajectory of depression that is so chronic, severe and disabling eventually may be altered for the betterment of so very many.…”
mentioning
confidence: 99%